PENYELENGGARAAN PAGELARAN OLAHRAGA BALAP DI SIRKUIT MANDALIKA SEBAGAI UPAYA PENINGKATAN NATION BRANDING INDONESIA - Havidz Ageng Prakoso; Vicky Rahmadana (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2022)
Indonesia experienced an economic recession during the Covid-19 pandemic, so the government tried to restore the national economy by doing various ways, such as by increasing nation branding. The implementation of racing sports, namely WSBK (World Super Bike) and MotoGP at the Mandalika Circuit, has great potential in improving Indonesia's nation branding. Therefore, this study aims to describe how the influence ofracing sports performances at the Mandalika Circuit on the improvement of Indonesia's nation branding. This study uses a qualitative descriptive research method using a conceptual framework, namely nation branding and sport tourism. The results obtained are that the WSBK and MotoGP performances at the Mandalika Circuit have succeeded in increasing Indonesia's nation branding at the international level, so that it has the potential to attract economic benefits from tourism and contribute to national economic recovery. The WSBK and MotoGP shows are great sport tourism opportunities for Indonesia in the future, because they not only improve the country's image in the international world but also have the potential to become a large foreign exchange contributorfor the country